2020
DOI: 10.1101/2020.07.03.20145995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Echocardiographic and Laboratory Findings in Coronary Slow Flow Phenomenon: cross-sectional study and review

Abstract: Background and aims Coronary Slow flow is a phenomenon known as slow contrast flow that injected into the coronary arteries, without epicardial coronary arteries obstruction. The etiology of this disease is unknown. Endothelial dysfunction, known as a major cause of Coronary Slow flow syndrome (CSF). Methods: This study was cross-sectional (descriptive-analytic), which was performed on patients admitted to Seyedoshohada Heart Center, during one year (2018-2019). Considering the inclusion and exclusion … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…According to Mohammadzad et al, [9], LVEF, IVSD, and E wave were considerably lower in the study group than the control group.…”
Section: Discussionmentioning
confidence: 66%
“…According to Mohammadzad et al, [9], LVEF, IVSD, and E wave were considerably lower in the study group than the control group.…”
Section: Discussionmentioning
confidence: 66%
“…Besides that, Seyyed Mohammadzad et al found that men, smokers, hypertensive individuals, and those with a high BMI had considerably higher rates of CSFP. Furthermore, the platelet count of these individuals was substantially higher [28].…”
Section: ) or -Odds Ratio CI -Confidence Interval Ht -Hypertension Hd...mentioning
confidence: 83%
“…Meanwhile, the CSF group had a higher BMI and SBP, with lower HDL, while there were no significant differences in the DBP, HTN, DM, family history of CAD, TG, TC, and LDL. The results of the CAG were pooled [ 9 , 17 , 20 , 22 , 25 , 26 , 30 , 33 , 34 , 37 ], suggesting that among the three coronary arteries, left anterior descending artery involvement was observed in 73% of patients, left circumflex artery involvement in 63%, and right coronary artery involvement in 54%. In 43% of patients with CSF, all three vessels were affected, while two-vessel and one-vessel diseases were observed in 31% and 26% of cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies, 2 were excluded from the meta-analysis because they did not report the measurement method of LVEF [ 24 , 34 ]. Twenty studies assessed LVEF using the modified biplane Simpson method; 1012 in the CSF group and 798 in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation